ANALYSIS OF EFFICIENCY OF PRODUCTION AT SMALL EMBOIDERY INDUSTRY IN REGENCY OF KUDUS - Zuhri, Saifudin; Zamzami, R. Mohd. (Universitas Pamulang, 2018)
This research aimed at analyzing factors influencing embroidery production and its efficiency at small emboidery industry in Kudus. A total respondent of this research was 108 taken using multi-stages sampling technique. In addition, 10 keypersons determined by purposive sampling were taken from competent stakeholders in embroidery business. Technical efficiency analysis by using stochastic Frontier Production Function was done to know the small embroidery industry whether it is efficient or not. The research findings showed that factors influencing the production of small embroidery industries in Kudus Regency consist of labor, raw materials, auxiliary materials, electricity, machinery and equipment, and they all have a positive and significant effect on the production of small embroidery industry. While the results of the calculation of production efficiency showedthat the level of technical efficiency of small embroidery industry doers in the research area is not efficient with an average value of less than 1 (0.9538).